2009
DOI: 10.1123/jsm.23.3.335
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Perceptions of Sexual Harassment by Sport Print Media Professionals

Abstract: While the impact of sexual harassment in the workplace has been well documented, little sexual harassment research has been conducted focusing on the women who work in the sport industry. This study explored the extent to which female sport print media professionals (i.e., sports editors, sportswriters, sports columnists) were subjected to sexually harassing behaviors in the workplace. Of the women who participated in the study (N= 112), over half of the participants indicated that they had encountered some fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…Some of the 57 females who encountered sexual harassment reported they faced physical form of sexual harassment: 27 incidents of unwelcome sexual advances and 14 incidents of physical conduct of a sexual nature. Data analysis of the satisfaction on the female sport media professionals had with the resolution of reported incidents of sexual harassment indicated that those who were less satisfied with negative consequences will impact job satisfaction (Pedersen, Osborne, Whisenant and Choong, 2009).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the 57 females who encountered sexual harassment reported they faced physical form of sexual harassment: 27 incidents of unwelcome sexual advances and 14 incidents of physical conduct of a sexual nature. Data analysis of the satisfaction on the female sport media professionals had with the resolution of reported incidents of sexual harassment indicated that those who were less satisfied with negative consequences will impact job satisfaction (Pedersen, Osborne, Whisenant and Choong, 2009).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…The respondents thus could not personally attribute causes of sexual harassment to shortfalls in their own company policies (Kariaga, 2010). Pedersen et al (2009) found incidents of sexual harassment being affected by attitudes toward sexual harassment. Those who responded with active attitudes towards sexual harassments were less likely to encounter incidents of sexual harassments.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Since its inception, women have struggled to break into sports journalism and build long and successful careers, and according to Lapchick et al (2013), today only about 12 percent of sports reporters and 10 percent of sports editors are women. Even when women do break into the profession, their outsider status is communicated to them in myriad ways; women regularly report feeling pressure to 'prove' their worth in a space in which their credibility and aptitude are regularly challenged (Whiteside and Hardin, 2013), and a study by Pedersen et al (2009) showed that more than half of the female sports reporters surveyed had experienced sexual harassment on the job. Furthermore, mainstream, national sports media outlets regularly marginalize women's sports, which conveys their outsider status (Cooky et al, 2013).…”
Section: Women and Sports Journalismmentioning
confidence: 99%
“…Grounded in hegemonic theory, this piece explores the operation of hegemonic masculinity or the 'pattern of practice' that naturalizes male privilege in various contexts -in this case, a framework of cultural norms that assumes men have a rightful ownership over sporting spaces (Connell and Messerschmidt, 2005: 832;also Duncan, 2006;Kane and Buysse, 2005). The construction of men as the sole embodiment of authentic athletes (and women as a subordinate Other) happens through myriad practices; in the workplace, women recognize their subordinate status through outright sexual harassment and their exclusion from highprofile men's sports assignments (Duncan, 2006;Pedersen et al, 2009;Ricchiardi, 2005). The overwhelming amount of men's sports content in sports media texts, combined with reporting practices that downplay female athletes' athleticism in favor of their femininity, also contribute to a wider process that establishes male authority in sports, thus justifying questions about women's place and status in those spaces (Cooky et al, 2013;Duncan, 2006).…”
Section: This Researchmentioning
confidence: 99%
“…Battenfield and Kent (2007) examined verbal communication, rituals, nonverbal communication, artifacts, and other aspects of communication in their investigation of the culture of communication in a sports information department. Other examples include sport industry employment topics pertaining to organizational issues such as referent comparison, job satisfaction, gender makeup and coverage trends, and sexual harassment of sport communication professionals (e.g., Pedersen, Osborne, Whisenant, & Lim, 2009; Pedersen, Whisenant, & Schneider, 2003; Whisenant, Pedersen, & Smucker, 2004).…”
Section: Focus: On Strategic Communication and Managementmentioning
confidence: 99%